Indonesia Menuju Pasar Bebas Asean Economic Community - Admiral Admiral (Jurnal Selat, 2015)
Indonesia is a part of the ASEAN that participatein to the free trade of ASEAN Economic Community, that effortto make ASEAN as a single market and production base, regional of high economy competitive eness and full integration on the global economy, in order to suppor tthe economic growth of the countries of the ASEAN. Indonesia expected to utilize the chance and ready to overcome the challenge of the ASEAN free trade Keywords : Indonesia, Free Trade, ASEAN